CLASSIFICATION STRAIN OF GENUS Actinobacillus, Haemophillus AND Pasteurella BASED ON NUMERICAL TAXONOMY METHOD - Retnowati, Yuliana (Sainstek, 2006)
The aim of this research was to classify strain of genus Actinobacillus, Haemophillus and Pasteurella based on numerical taxonomy through Simple Matching Coefficient (SSM) and Jaccard Coefficient ( SJ ) analyze. Fifty character units of thirds genus were collected from Bergeys manual compiled in n x t matrix. Phena was detected based on taxospecies concept. MVSP Plus version 2.0 and UPGMA algorithm was used to construct of similar matrix and dendogram. The result of this research are classified the genus Actinobacillus, Haemophillus and Pasteurella into 4 (four) clusters through SSM analyze and 10 (ten) clusters through SJ analyze with coefficient correlation 0.4055 (SSM) and 0.824 (SJ). It show that the dendogram was constructed from SJ analyze more accurate than SSM analyze.